Pengendalian Hipertensi Menggunakan Tanaman Obat Keluarga di Kelurahan Lebak Bandung - Fithriyani Fithriyani; Vevi Suryenti Putri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Hypertension or high blood pressure is characterized by increased blood pressure. The incidence of hypertension continues to increase, the dangers of complications that arise, and the risks of long-term pharmacological treatment. The prevalence of hypertension tends to increase recently. Hypertension that is not treated properly has a high risk of complications including stroke, pulmonary edema, heart attack, and kidney failure. One of the efforts to prevent complications of hypertension is by controlling blood pressure regularly and controlling hypertension, one of which is by using family medicinal plants (TOGA) which are widely grown around residents' homes. The method of activities carried out is in the form of socialization by providing counseling on how to control hypertension by utilizing TOGA. Implementation of activities carried out on residents in the Lebak Bandung Village, Jambi City. The purpose of this activity is to provide an understanding to residents about how to control hypertension through TOGA and can apply it in their respective yards